British naval strategy east of Suez, 1900-2000 : influences and actions - Kennedy, Greg (Cass series--naval policy and history, 2005)
This new collection of essays by a panel of established international scholars sheds new light on what some of those influences were and what actions were taken as a result of Britain's Far Eastern commitments. Not only are new evidence and approaches to those issues addressed presented, but new avenues for further research are clearly outlined. This new study shows how the use of the sea as a means of projecting power and influence beyond national borders holds a unique place in the history of Great Britain. Directly linked to the concepts of empire, great power and strategic over-s.